2016
DOI: 10.1530/eje-15-0972
|View full text |Cite
|
Sign up to set email alerts
|

GEP- NETS UPDATE: Genetics of neuroendocrine tumors

Abstract: Neuroendocrine tumors (NETs) are a heterogeneous group of neoplasms, arising from neuroendocrine cells that are dispersed throughout the body. Around 20% of NETs occur in the context of a genetic syndrome. Today there are at least ten recognized NET syndromes. This includes the classical syndromes: multiple endocrine neoplasias types 1 and 2, and von Hippel-Lindau and neurofibromatosis type 1. Additional susceptibility genes associated with a smaller fraction of NETs have also been identified. Recognizing gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 163 publications
(184 reference statements)
1
71
0
3
Order By: Relevance
“…The vast majority of pNETs are sporadic, and genes involved in the hereditary disorders have also been attributed to sporadic pNET (Crona & Skogseid 2016). Two studies using nextgeneration sequencing (NGS) revealed alterations; among those, MEN1 and ATRX/DAXX alterations were the most frequent ones ( (Tang et al 2016).…”
Section: Pancreatic Neuroendocrine Tumors (Pnet)mentioning
confidence: 99%
“…The vast majority of pNETs are sporadic, and genes involved in the hereditary disorders have also been attributed to sporadic pNET (Crona & Skogseid 2016). Two studies using nextgeneration sequencing (NGS) revealed alterations; among those, MEN1 and ATRX/DAXX alterations were the most frequent ones ( (Tang et al 2016).…”
Section: Pancreatic Neuroendocrine Tumors (Pnet)mentioning
confidence: 99%
“…6 Epitope prediction on peptides containing these SNVs and on neoORF peptides generated by frameshift indels, revealed 28 epitopes that bind with high to intermediate affinity to one of the patient's HLA allele. We then synthesized these predicted neoantigens together with the corresponding wildtype peptides and conducted IFNg ELISpot assays using the patient's peripheral blood to asses if there are T cells that are reactive against them.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of somatic genetic alterations have also been described for various NETs, hindgut NETs however remain poorly characterized. 4,6,7 Generally, NET genomes harbor relatively few somatic mutations when compared with adenocarcinomatous tumors. 6 NETs present a wide spectrum of malignancies from relatively indolent to highly aggressive variants.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations